The Effect of Going Public on Innovative Productivity and Exploratory Search - Wu, Geraldine A. (Organization Science, 2012)
This paper investigates whether and how going public affects firm innovation. I propose that initial public offerings (IPOs) fundamentally reshape core organizational structures and processes, and I consider implications for firms' overall innovative productivity and their exploratory search strategies. Using longitudinal data on U.S. medical device firms funded by venture capital and inverse probability of treatment weights to account for self-selection into IPOs and the presence of time-dependent confounders, I find that a firm's overall innovative productivity increases after the firm goes public. Going public also decreases the proportion of innovation search that explores new and recently developed knowledge and increases the proportion of exploratory search building on scientific knowledge. Estimates represent population average treatment effects.